PHENOLIC ACID PROFILING BY RP-HPLC: EVALUATION OF ANTIBACTERIAL AND ANTICANCER ACTIVITIES OF CONOCARPUS ERECTUS PLANT EXTRACTS - Khalil, R; Ali, Q; Hafeez, MM; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
Due to the versatile application of plants the utilization of plants and their inferred substances builds up day by day for the revelation of new curative agents. Conocarpus erectus has placed in the family Combretaceae, in one of the two species of Conocarpus genus and ordinarily exists in tropical and subtropical regions of the world. In some countries it is used as folk medicine for fever, anemia, diabetes, catarrh, diarrhea and conjunctivitis. The current study was carried out to investigate the antibacterial and anticancer properties of the plant. The four defatted methanol extracts of C. erectus different parts (leaves, stems, fruits and bark) showed high antibacterial and anticancer activity even with small quantity of dose. Antimicrobial assay was used to check out the antibacterial activity against 6 bacterial strains Escherichia coli, Staphylococcus Aureus and Klebstella Pneumoniae. The results show that gram positive bacteria show more sensitivity and zone of inhibition as compared to gram negative bacteria. For anticancer activity, MTT assay was performed on HepG2 cells for this purpose. Plant extorts show anticancer activity with a minute quantity. For phytochemical screening defatted methanol extract of Conocarpus erectus was subjected to the silica gel glass column go behind by (RP-HPLC–UV–ESI-MS). It contains phenol such as tannin and flavinoid as major component. Plant contain Ellagic acid; di-hexahydroxy diphenyl, Vascalgin isomer as foremost tannin component. Gallic Acid, Kaempferol on the base of mass spectra and time of retention. The extract of Conocarpus erectus (leaves, shoot, bark & fruit) parts shows high antibacterial, antioxidant and hepta-protective activities due to phenolic content. Tannin has high antibacterial activity than other compound. C.erectus is notable for its folkloristic curative potential. More in vivo and in vitro phytochemical studies are needed to use the plant for prevention and treatment of many diseases.